Modeling children's behavioral problems based on parenting methods with parent-child relationship mediation - Moradi , Mahboobeh; Farhangi , Abdolhassan; Tizdast , Taher (Applied Family Therapy Journal (AFTJ), 2023)
Aim: The present research was conducted with the aim of modeling children's behavioral problems based on parenting methods with the mediation of parent-child relationship. Methods: In a cross-sectional study in the form of a correlational design, all mothers of primary school students with behavioral problems in Karaj city were selected using a simple random sampling method from the list of names of students diagnosed with behavioral problems. After obtaining informed consent, the research data were used with the help of the Achenbach Child Behavior Checklist (CBCL) - Achenbach and Rescorla (2001), parenting style questionnaire (1973) and Pianta parent-child relationship questionnaire (2015). In order to check the assumptions of the statistical tests and test the hypotheses of the research, using the SmartPLS software, the identified paths of the research have been investigated according to the conceptual model. Version 3.3 of SmartPLS software was used to compile the confirmatory factor analysis model and structural equations, and SPSS version 26 was used for descriptive statistics. Path analysis has also been used to determine direct and indirect coefficients. Results: The results obtained from the bootstrap method and the Sobel test both show that the indirect effect of parenting methods on children's behavioral problems due to the parent-child relationship is -0.298, and the value of the Sobel statistic is significant at the 95% confidence level. (Sobel = 5.28, P